2021
DOI: 10.3389/fonc.2021.603070
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and Biological Behavior of Gastric Signet-Ring Cell Carcinoma Better or Worse: A Meta-Analysis

Abstract: BackgroundThe clinical pathology of gastric signet-ring cell carcinoma (SRC) is still unclear. This meta-analysis was performed to evaluate the difference in biological behavior and prognosis between SRC and non-signet ring cell carcinoma (NSRC).MethodsA total of 58 eligible studies were analyzed using RevMan and other auxiliary software. Biological behaviors were compared based on odds ratio (OR) and mean difference (MD). Hazards ratio (HR) was calculated for prognosis based on Kaplan–Meier curves.ResultsTota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…It has been clinically reported that SRC patients have a worse prognosis than non-SRC AGC patients. 8 One cause of this may be the development of chemotherapy drug resistance in SRC patients. Understanding chemotherapy drug-resistance mechanism is important for the development of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been clinically reported that SRC patients have a worse prognosis than non-SRC AGC patients. 8 One cause of this may be the development of chemotherapy drug resistance in SRC patients. Understanding chemotherapy drug-resistance mechanism is important for the development of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…SRC gastric accounts for approximately 3.4% to 50% of gastric cancer cases. 5 , 7 , 8 SRCs have a small nucleus on one side and a cytoplasm that is full of mucus and rarely form lines or coronary structures. The prognosis of SRC gastric cancer is different in early and advanced stages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, we found that the expression level of AADAC was high in the Kato III GC cell line with signet ring cell carcinoma (SRC). SRC, a special pathological type, has a good prognosis in EGC and a poor prognosis in AGC [ 45 , 46 ]. It may suggest that driver mutations controlling the metastatic potential of SRC can occur late in GC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, gastric signet ring cell carcinoma (GSRC), which is named because a large amount of mucus in cancer cells pushes the nucleus to one side like a ring, is one of the most malignant tumors, accounting for about 3.4%-39% of GC [ 5 , 6 ]. Though the incidence of GC has declined in the world since the active treatment of Helicobacter pylori , the incidence of GSRC is still increased significantly [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%